2005
DOI: 10.1016/j.apmr.2005.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density After Spinal Cord Injury: A Reliable Method for Knee Measurement

Abstract: Objectives-To test the interrater reliability of a standardized method to analyze knee bone mineral density (BMD) using dual-energy x-ray absorptiometry (DXA); to compare spine, hip, and knee BMD of people with spinal cord injury (SCI) with able-bodied controls; and to determine the relation between hip BMD and knee BMD in SCI and able-bodied subjects. Design-Criterion standard and masked comparison. Setting-Primary care university hospital.Participants-A convenience sample of 11 subjects with complete SCI was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 22 publications
1
42
0
1
Order By: Relevance
“…The DXA scan (Lunar iDXA, EnCORE software version 13.31.016, GE Medical Systems; Madison, Wisconsin) was performed to obtain regional measurements of BMD at the proximal femur, distal femur, and proximal tibia. The proximal femur was scanned according to the manufacturer specifications and the distal and proximal tibia regions were scanned according to the methods described by Shields et al [28]. The study was discussed with the participants, and they were provided ample opportunity to ask questions.…”
Section: Participantsmentioning
confidence: 99%
“…The DXA scan (Lunar iDXA, EnCORE software version 13.31.016, GE Medical Systems; Madison, Wisconsin) was performed to obtain regional measurements of BMD at the proximal femur, distal femur, and proximal tibia. The proximal femur was scanned according to the manufacturer specifications and the distal and proximal tibia regions were scanned according to the methods described by Shields et al [28]. The study was discussed with the participants, and they were provided ample opportunity to ask questions.…”
Section: Participantsmentioning
confidence: 99%
“…Although the standard clinical protocol by DXA for assessing BMD involves the hip and spine, 8 it does not routinely measure the knee/leg where fractures are more likely to occur. [1][2][3][4][5] There have been some advances to refine the use of DXA at the distal femur and proximal tibia; Shields et al 14 have reported the reliability of a DXA protocol for assessment of BMD around the knee. Importantly, establishing normative data for BMD with a DXA-knee protocol is crucial for the future assessment of bone health for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Technicians identified the regions of interest, and analytic software automatically performed BMD calculations. For the distal femur and proximal tibia, the lumbar spine algorithm as described by Shields et al 18 was used. Manual image correction was performed to include all appropriate bone pixels.…”
Section: à2mentioning
confidence: 99%